Dry Reforming of Methane over Mn-modified Ni-based Catalysts - Manabayeva, Alua M. (Springer, 2025)
Ni-based bi- and trimetallic Mn, Mg and aluminum containing catalysts prepared by the solution combustion synthesis (SCS) method were tested in dry reforming of methane (DRM). As a comparison 12 wt.% Ni/α-Al2O3 catalyst prepared by wet impregnation was also investigated. The catalysts were characterized by means of XRD, N2 physisorption, H2-TPR, CO2-TPD, NH3-TPD, TPO, CHNS, TGA, SEM and TEM. Formation of crystalline MnAl2O4 was observed at high temperatures during SCS. The average nickel particle size varied in the range of 12–36 nm. Addition of Mn promoted reduction of Ni and elevated the amount and strength of the basic sites.